The Use of Fish Scale Hormone Concentrations in the Assessment of Long-Term Stress and Associated Adverse Effects on Reproductive Endocrinology - Emily K. C. Kennedy; David M. Janz (Fishes, 2022)
Investigation of the use of fish scales as a medium for non-lethal biomonitoring has recently commenced. Fish scales have been shown to incorporate cortisol over longer periods of time than blood and thus provide a promising means of assessing long-term stress in many species of teleost fish. However, while cortisol is a major mediator of the stress response in fishes, downstream effects of chronic stress on reproduction can involve gonadal steroids such as progesterone and testosterone. The quantification of these additional hormones alongside cortisol could therefore allow for the assessment of both stress and consequential reproductive alterations. To investigate these concepts, we artificially elevated circulating cortisol, progesterone, and testosterone in rainbow trout (Oncorhynchus mykiss) using coconut oil implants for three weeks. Following this we quantified these three hormones as well as 11-ketotestosterone, a potent androgen in teleost fishes. In all cases serum samples reflected a significant increase in the injected hormone confirming the efficacy of this method; however, this did not result in significantly elevated scale concentrations of the same hormone in all cases. As the stress and reproductive axes are closely integrated, these findings are likely a result of interactions along the steroidogenic pathway indicating that a further investigation of the relationship between scale concentrations of these hormones and actual physiological processes is required. Nevertheless, the successful quantification of both stress and gonadal steroid hormones within the scale suggests that such measurements could provide a novel and informative tool in the assessment of long-term stress and the resulting effects on reproductive endocrinology in teleost fishes.